DEV-02. CLINICAL FEATURES OF 1027 TUMORS OF CENTRAL NERVOUS SYSTEM IN CHILDREN: SINGLE INSTITUTIONAL REPORT FROM SHANGHAI XINHUA HOSPITAL, THE FOUNDING MEMBER OF CNOG. Issue 2 (22nd June 2018) - Han, Yipeng; Zhao, Yang; Jiang, Feng; Li, Qifeng; Wang, Baocheng; Zhang, Chenran; Ma, Jie
Abstract: BACKGROUND: Central nervous system (CNS) tumor is the most common solid neoplasm in children. Here we report clinical features of children with CNS tumor treated in our institute during recent 10 years. METHODS: Retrospective study was conducted in children with CNS tumor treated in Xinhua Hospital Affiliated to Shanghai Jiaotong University School of Medicine, during 2006 to 2016. Clinical data were collected. Statistical calculation was conduct for characteristic analyses. RESULTS: 1027 cases of CNS tumor in children were collected, with 611 males and 336 females. Age ranges were 10.22% in infants (< 1 y/o), 27.07% in toddler (1 - 3 y/o), 35.15% in preschool children (3 - 7 y/o), 26.78% in school-age children (7 - 15 y/o) and 0.78% in adolescence (> 15 y/o). 423 cases were diagnosed with WHO I-II grades and 367 cases were with WHO III-IV grades. There were 538 supratentorial tumors and 424 subtentorial tumors. The most common tumor type was pilocytic astrocytoma (n=141, 13.80%), followed by medulloblastoma (n=132, 12.92%). CONCLUSIONS: The gender ratios in different age ranges were stable, with high incidence in male than in female. In total, low grade tumors were more common than high grade tumors. Pilocytic astrocytoma was most common tumor, followed by medulloblastoma.